Comparison of the Serodia Treponema pallidum Particle Agglutination, Captia Syphilis-G, and SpiroTek Reagin II Tests with Standard Test Techniques for Diagnosis of Syphilis - Pope, Victoria (American Society for Microbiology, 2000)
We compared the microhemagglutination assay for Treponema pallidum (MHA-TP), a treponemal test, with two other treponemal tests, the Serodia Treponema pallidum particle agglutination (TP-PA) assay and the Captia Syphilis-G enzyme immunoassay, using 390 clinical serum samples. We also compared two nontreponemal tests, the rapid plasma Reagin (RPR) card test and the SpiroTek Reagin II test. Agreements of the MHA-TP with the TP-PA test and the Syphilis-G test were 97.4 and 97.7%, respectively. There was 89.2% agreement between the RPR and Reagin II tests. The Reagin II test was more apt to be reactive if the treponemal test was also reactive. We conclude that either the Serodia TP-PA test or the Captia Syphilis-G test is an appropriate substitute for the MHA-TP and that the Spirotek Reagin II test could substitute for the RPR test as a screening test.